Intestinal inflammation marker calprotectin regulates epithelial intestinal zinc metabolism and proliferation in mouse jejunal organoids - González, R.; Ceacero-Heras, D.; Tena-Garitaonaindia, M.; Álvarez-Mercado, A.; Gámez Belmonte, Maria de los Reyes; Chazin, W. J.; Sánchez de Medina, F.; Martínez-Augustin, O. (Biomedicine & Pharmacotherapy, 2024)
Calprotectin (CP), a heterodimer of S100A8 and S100A9, is expressed by neutrophils and a number of innate immune cells and is used widely as a marker of inflammation, particularly intestinal inflammation. CP is a ligand for toll-like receptor 4 (TLR4) and the receptor for advanced glycation end products (RAGE). In addition, CP can act as a microbial modulatory agent via a mechanism termed nutritional immunity, depending on metal binding, most notably Zn2+. The effects on the intestinal epithelium are largely unknown. In this study we aimed to characterize the effect of calprotectin on mouse jejunal organoids as a model epithelium, focusing on Zn2+ metabolism and cell proliferation. CP addition upregulated the expression of the Zn2+ absorptive transporter Slc39a4 and of methallothionein Mt1 in a Zn2+-sensitive manner, while downregulating the expression of the Zn2+ exporter Slc30a2 and of methallothionein 2 (Mt2). These effects were greatly attenuated with a CP variant lacking the metal binding capacity. Globally, these observations indicate adaptation to low Zn2+ levels. CP had antiproliferative effects and reduced the expression of proliferative and stemness genes in jejunal organoids, effects that were largely independent of Zn2+ chelation. In addition, CP induced apoptosis modestly and modulated antimicrobial gene expression. CP had no effect on epithelial differentiation. Overall, CP exerts modulatory effects in murine jejunal organoids that are in part related to Zn2+ sequestration and partially reproduced in vivo, supporting the validity of mouse jejunal organoids as a model for mouse epithelium.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Calprotectin; Intestinal epithelium; Intestinal inflammation markers; Organoid; Proliferation; Zinc